2009
DOI: 10.1002/path.2582
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced number and activity of mitochondria in multiple sclerosis lesions

Abstract: Mitochondrial dysfunction has been implicated in the development and progression of multiple sclerosis (MS) lesions. Mitochondrial alterations might occur as a response to demyelination and inflammation, since demyelination leads to an increased energy demand in axons and could thereby affect the number, distribution and activity of mitochondria. We have studied the expression of mitochondrial proteins and mitochondrial enzyme activity in active demyelinating and chronic inactive MS lesions. Mitochondrial prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
147
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 184 publications
(161 citation statements)
references
References 49 publications
9
147
0
5
Order By: Relevance
“…Studies of postmortem multiple sclerosis brains have described increased mitochondria volume in axons that are likely to be demyelinated for years or decades (14,42). We establish here that increased axonal mitochondrial volume occurs within days (slice cultures) or weeks (mice) of demyelination, and that this increase is caused by increased sizes of mitochondrial stationary sites.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Studies of postmortem multiple sclerosis brains have described increased mitochondria volume in axons that are likely to be demyelinated for years or decades (14,42). We establish here that increased axonal mitochondrial volume occurs within days (slice cultures) or weeks (mice) of demyelination, and that this increase is caused by increased sizes of mitochondrial stationary sites.…”
Section: Discussionmentioning
confidence: 66%
“…The cuprizone dose used in the present study does not cause changes in mitochondrial structure in CNS axons. Although we cannot rule out cuprizone-induced changes in mitochondrial function, increased mitochondrial size/volume in demyelinated axons has been reported in multiple studies regardless of the cause of demyelination (14,17,(40)(41)(42). The mitochondrial changes described following cuprizone-induced demyelination in vivo were also found following lysolecithin-induced demyelination in vitro.…”
Section: Discussionmentioning
confidence: 68%
“…Profound mitochondrial disturbances have been found in MS lesions by microarray based gene expression analysis [26,27], by immunohistochemistry, biochemical analysis and by electron microscopy [26,79,112]. In acute and active lesions first changes in mitochondria are reflected by a dominant loss of immunoreactivity of cytochrome C oxidase (COX1) and loss of the respective complex IV activity of the mitochondrial respiratory chain [79].…”
Section: Mitochondrial Injury In Ms Lesionsmentioning
confidence: 99%
“…These spontaneous improvements may reflect either restored mitochondrial activity or a compensatory increase in the number of mitochondria. Histopathological studies found increased numbers of mitochondria and an upregulation of mitochondrial cytochrome C oxidase (complex IV) in axons in both chronic lesions and normal appearing white matter of MS subjects (Mahad et al, 2009;Witte et al, 2009). …”
Section: Axonal Energy Metabolismmentioning
confidence: 99%